The Impact of Peer Corrective Feedback toward Descriptive Writing Quality of Junior High School Students - Sindhy Melinda (Graduate Program, University of Islam Malang, 2020)
This study aimed to investigate the effectiveness of giving corrective feedback through peers and teacher in writing paragraph description of junior high school students. The initial sample in this study included 50 students which divided into two groups, experimental group and control group. In peer-corrective feedback group, the correction code was carried by their peers who assessed the paragraph using Chandler's composition model as the coding descriptor. In teacher corrective feedback group was carried by the teacher also using Chandler's composition model as the coding descriptor. Then both score of students’ paragraph are given score by the teacher by using the composition reference by Jacobs et al. In this study the use T-test is to investigate differences in writing results obtained by students before and after providing corrective feedback from friends and teachers. This finding also revealed to find out the aspects that improve the most after the implementation of peers and teacher feedback. Giving feedback in this study is more focused on grammar and mechanics, paragraph content, vocabulary, and organization. Students also revealed that giving feedback by peers and teacher had a positive impact on the ability in writing their paragraphs and it also could exchange insights with friends.